Soil physical attributes in integrated bean and sheep system under nitrogen levels - Andreolla, Veruschka (2014)
Integrated crop-livestock systems (ICLS) can promote higher grain and meat/milk yield as well as reduce soil degradation risks. Thus, this study aimed to evaluate the influence of grazing sheep with moderate intensity and nitrogen doses on soil physical attributes, and bean crop yield (Phaseolus vulgaris Lam.) under rotation with summer corn crop (Zea mays Lam.) and winter pasture with oats (Avena sativa Lam) and ryegrass (Lolium multiflorum Lam.) The experimental design was completely randomized blocks with split-plot; the plots were nitrogen doses and the split-plots were grazing presence or absence. The treatments were nitrogen doses of 0, 75, 150 and 225 kg ha-1 applied on ryegrass and white oat pasture in winter followed by bean crop. Soil density, macroporosity, microporosity and total porosity and bean grain yield were evaluated. When ICLS are managed under no-tillage with moderate grazing, sheep trampling did not affect negatively soil physical attributes, which did not reach critical levels for subsequent growth and development of the bean crop. The black bean yield in summer was not affected by antecedent presence of sheep grazing in winter.